Vitamin D and Gestational Diabetes Mellitus: A Literature Review - Rista Dwi Hermilasari (Universitas Jenderal Achmad Yani Yogyakarta, 2023)
Background: Gestational diabetes mellitus (GDM) is one of public health concerns that can increase risk of harmful pregnancy outcome. Diabetes in pregnancy often associated with vitamin D level, it means that lack of vitamin D in pregnancy could raise the risk of gestational diabetes.Objective: To describe the vitamin D blood level and pregnancy-related gestational diabetes incidence.Methods: This literature review was taken from PubMed and Science Direct database. Screening of reviewed article based on inclusion and exclusion criteria.Results: Seven articles that had been reviewed said pregnancy with gestational diabetes mellitus had lower 25(OH)D serum level than in non GDM group. The proportion of pregnant women which are sufficient of vitamin D is very low.Conclusion: Pregnancy-related low vitamin D levels are linked to an elevated risk of gestational diabetes mellitus. Sufficient vitamin D levels are protective against GDM